Penyuluhan Komunikasi dalam Antisipasi Efek Negatif Pemaparan Pornografi di Media Online dan Pengaruhnya Terhadap Perilaku Generasi Milenial Desa Sungai Ulak - Satria, Deni (PT. Meja Ilmiah Publikasi, 2024)
This community service program aims to provide counseling to anticipate the negative impact of exposure to pornography on online media and its effects on adolescent behavior. The activity focuses on the millennial generation in Sungai Ulak Village, Merangin Regency, which is vulnerable to pornographic content due to easy digital access. The counseling was carried out by providing digital literacy and interactive communication methods to raise adolescents' awareness of the dangers of pornography. The results of the activity showed that many adolescents did not fully understand the negative impacts of pornography on their behavioral development. This counseling provided new insights and increased awareness of the importance of content selection on online media. In addition, the results of this activity are expected to serve as a reference in teaching Cyber Law courses. It is hoped that similar programs will continue to strengthen the younger generation's understanding of healthy digital literacy.